2020
DOI: 10.1097/icl.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Activity of Multipurpose Disinfecting Solutions in the Presence of Different Organic Soils

Abstract: Objective: During use, contact lens disinfecting solutions are exposed to tears and clinical microbial isolates. The current study was designed to test the performance of several disinfecting solution in the presence of organic soils or clinical isolates. Methods: Standard and clinical isolates were exposed to the disinfecting solutions in the presence or absence of different organic soils. The number of microbial cells killed during disinfection was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…48 A recent study has also confirmed that P-I is effective against clinical isolates of bacterial species (P. aeruginosa from a patient with MK; and S. marcescens and Achromobacter xylosoxidans from CL cases), even in the presence of organic soils, and reports no adverse events due to P-I. 13 Furthermore, a study comparing a P-I MPS to a PQ-1 plus PHMB MPS found they were both effective against in vitro planktonic bacteria (standard strain S. marcescens; and clinically isolated P. aeruginosa, Delftia acidovorans, Stenotrophomonas maltophilia, S. aureus, and S. epidermidis), but only P-I was effective against biofilms isolated from CL cases. 85 Studies have also proven P-I is effective against in vitro clinically isolated 86 and known pathogenic 87,88 strains of Acanthamoeba cysts and trophozoites.…”
Section: Povidone-iodinementioning
confidence: 84%
See 1 more Smart Citation
“…48 A recent study has also confirmed that P-I is effective against clinical isolates of bacterial species (P. aeruginosa from a patient with MK; and S. marcescens and Achromobacter xylosoxidans from CL cases), even in the presence of organic soils, and reports no adverse events due to P-I. 13 Furthermore, a study comparing a P-I MPS to a PQ-1 plus PHMB MPS found they were both effective against in vitro planktonic bacteria (standard strain S. marcescens; and clinically isolated P. aeruginosa, Delftia acidovorans, Stenotrophomonas maltophilia, S. aureus, and S. epidermidis), but only P-I was effective against biofilms isolated from CL cases. 85 Studies have also proven P-I is effective against in vitro clinically isolated 86 and known pathogenic 87,88 strains of Acanthamoeba cysts and trophozoites.…”
Section: Povidone-iodinementioning
confidence: 84%
“…Studies have found that the efficacy of MPS against ISO standard strains may differ in the presence of organic soil. [11][12][13] Organic soil found in the tear film may be transferred from a removed CL into a MPS and may neutralize the disinfecting agent. 9 The FDA standards require proof of efficacy against a laboratoryprepared organic soil composed of a mixture of killed Saccharomyces cerevisiae and inactivated fetal bovine serum.…”
Section: Preservatives In Mps -Standardizations For Efficacy and Safetymentioning
confidence: 99%
“…This is an obvious difference from other multipurpose disinfecting solution and hydrogen peroxide–based products. A recent study investigating the antimicrobial efficacy of contact lens care products in the presence of the model tear organic soil reported that multipurpose disinfecting solution was significantly affected by the organic soil, unlike the solution containing povidone-iodine, which maintained its activity 48 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigating the antimicrobial efficacy of contact lens care products in the presence of the model tear organic soil reported that multipurpose disinfecting solution was significantly affected by the organic soil, unlike the solution containing povidone-iodine, which maintained its activity. 48 These experiments have demonstrated that the number of bacteria in lens storage cases can be significantly reduced if appropriate lens and lens case hygiene is performed. Therefore, contact lens users should be recommended to, at a minimum, rinse and air-dry their lens cases when using cleadew and rinse, tissue-wipe, and air-dry when using Biotrue after contact lens disinfection.…”
Section: Article Informationmentioning
confidence: 98%
“…[19][20][21][22] The PVP-I system is an innovative disinfecting solution compared with an MPDS from the perspective of disinfecting efficacy, including stand-alone tests, biofilm, and lens surface or lens case contamination. 6,[23][24][25] Thus, in Japan, PVP-I system for rigid lenses is currently recommended for the care of orthokeratology lenses in the orthokeratology guidelines developed by the Japan Contact Lens Society. 26 In fact, the number of PVP-I system users is steadily increasing year by year.…”
mentioning
confidence: 99%